PENDAMPINGAN PENGEMBANGAN MATERI KEAGAMAAN ISLAM DI MADRASAH MA’ARIF SAMARINDA - Darwis, Darwis; Wardhana, Kautsar Eka; Setiawan, Agus (FIKRUNA: Jurnal Ilmiah Kependidikan dan Kemasyarakatan, 2024)
This community service activity aims to support the development of Islamic religious education materials at Ma’arif Islamic School (Madrasah Ma’arif) in Samarinda through a participatory approach. The background of this initiative is based on the need to renew and strengthen Islamic Education materials in alignment with the values of Ahlussunnah wal Jamaah, the local needs of the Muslim community in Samarinda, and contemporary socio-religious challenges. The implementation method uses a Participatory Action Research (PAR) approach, consisting of the preparation phase (needs analysis), implementation phase (observation, discussions, and drafting of materials), and the evaluation and monitoring phase. The results of the activity showed an increase in the knowledge of teachers, school principals, and parents about the importance of contextual and practical religious education materials. In addition, students showed improved confidence in memorizing and practicing religious materials, and there was an increased level of trust from the community toward Madrasah Ma’arif as a credible Islamic educational institution. The developed materials include daily prayers, short surahs, prayer recitations, and selected hadiths tailored to the students’ life context. This activity demonstrates that the participatory-based development of religious materials can enhance the quality of Islamic education and increase the involvement of various stakeholders in supporting relevant and moderate religious education.